Digital marketing in active sports tourism: Enhancing the quality of services for tourism companies in the hail region - Ismail, Ahmed Galal Selim; Bakheet, Salwa Mohamed Mohamed; Mahran, Kamal Abdelgaber; Mohammed, Ahmed F A (International Journal of Management and Sustainability, 2025)
The primary objective of this study was to determine the role of digital marketing strategy in increasing tourism companies’ services regarding active sports tourism. Data was collected through 307 questionnaires filled out by managers and employees in the Hail region of the Kingdom of Saudi Arabia. The results showed that digital marketing improves service quality. However, there are serious issues related to customer awareness and customer satisfaction or dissatisfaction. It was also found that there are some major barriers to the successful implementation of digital marketing, including low awareness of the need for digital marketing, insufficient funding by sponsors and promoters, and lack of adequate training in the use of marketing tools. The study indicates that more qualitative studies in future studies are still needed in other areas, including evaluating consumer responses to digital marketing campaigns, enhancing the use of technology in customer satisfaction, and evaluating different types of media to win consumers. Developing a dedicated digital platform for sports tourism can help attract a niche market of active tourists by offering tailored content and experiences. Providing employees with adequate training in digital marketing tools and techniques is essential to overcome skill gaps.